2019
DOI: 10.1136/bmjopen-2019-029469
|View full text |Cite
|
Sign up to set email alerts
|

Complex intervention in augmentative and alternative communication (AAC) care in Germany: a study protocol of an evaluation study with a controlled mixed-methods design

Abstract: IntroductionThe current practice of service delivery in Germany for people with complex communication needs (CCN) who are in need of augmentative and alternative communication (AAC) is characterised by diverse problems, including a lack of clarity in the responsibilities of the service providers involved. To address these issues a new service delivery model has been put in place, implemented in three AAC counselling centres for patients with a particular health insurance across Germany. The implementation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…All components of the intervention and comparison groups were managed by the three AAC consultation centers participating in the project. 29 The formal caregivers (eg, teachers or speech and language pathologists) and informal caregivers (eg, parents or relatives) of the AAC users in the intervention group and in the comparison group were surveyed at three timepoints (T0=after initial AAC assessment and consultation; T1=4 weeks after AAC system receipt [after AAC training]; and T2=3 months after AAC system receipt [after AAC therapy]). Additionally, focus group interviews were conducted with informal and formal caregivers and AAC consultants of the intervention group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All components of the intervention and comparison groups were managed by the three AAC consultation centers participating in the project. 29 The formal caregivers (eg, teachers or speech and language pathologists) and informal caregivers (eg, parents or relatives) of the AAC users in the intervention group and in the comparison group were surveyed at three timepoints (T0=after initial AAC assessment and consultation; T1=4 weeks after AAC system receipt [after AAC training]; and T2=3 months after AAC system receipt [after AAC therapy]). Additionally, focus group interviews were conducted with informal and formal caregivers and AAC consultants of the intervention group.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the intervention aimed to standardize AAC care and to improve the implementation of AAC among all stakeholders. 29 The structure of the intervention and the involved active and passive stakeholders are presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Details on the German AAC and insurance system and the research project design can be found in the published study protocol. 31 …”
Section: Methodsmentioning
confidence: 99%
“…Practice partners from the cooperating counselling centres 31 with a lot of experience working with people who use aided AAC were involved in the planning, recruitment and instrument development of the study via regular meetings. A person who uses aided AAC is part of the team in one cooperating counselling centre and has also provided advice.…”
Section: Methodsmentioning
confidence: 99%
“…This is because customizing these alternative access methods largely fails to fully address or compensate for the access barriers that individuals with severe motor impairments often face. Poor technical knowledge amongst caregivers and support staff (e.g., due to limited training [ 5 ]) and precise mounting requirements that necessitate manual device adjustments [ 6 ] are among the largest barriers to communication, despite these individuals being matched to a device that best fits their residual motor capabilities and use preferences [ 7 , 8 ]. Because of this, AAC users that require both alternative access and augmentative speech options are often excluded from successful use of AAC devices [ 9 - 11 ], contributing to the nearly one-third of patients who abandon their clinically prescribed AAC device in favor of less-effective dysarthric speech or manual gestures, among other communication methods [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%